IMPLEMENTASI KURIKULUM MERDEKA TERHADAP MOTIVASI BELAJAR SISWA PADA MATA PELAJARAN EKONOMI SMAN 1 SEBANGKI - Tilawati, Tilawati; Matsum, Junaidi H.; Budiman, Jumardi (Universitas Tanjungpura, 2025)
This study examines how the implementation of the Independent Curriculum influences students' learning motivation at SMAN 1 Sebangki. Using a qualitative case study approach, data were collected through interviews, observations, and documentation, involving nine informants: the principal, vice principal of curriculum, an economics teacher, and students. The findings indicate that since its implementation in the 2022/2024 academic year, the Independent Curriculum has positively impacted students